Photochemical synthesis of 7,14-dialkynyl-10,11-dimethyl[5]helicene via flow chemistry and comparison with its bromo analog - Uhlmann, Anselm; Guyon, Jacques; Werz, Daniel B. (Synlett)
A flow photoreactor for the photochemical synthesis of substituted [5]helicenes from corresponding distilbenes is described. This method allows to circumvent scale limitations often associated with such reactions due to the high dilutions required. Additionally, reaction times can be significantly reduced by utilizing flow conditions. The syntheses of both, a known bromo-substituted helicene and a novel alkynyl-substituted helicene are compared for both, batch and flow.